Pengaruh Kualitas Pelayanan, Kelengkapan Produk, dan Harga Terhadap Minat Beli Konsumen di Toserba Laris Kartasura - Tiara Kartika Sari; Intana Wahyu Putri; Rayhan Gunaningrat; R Taufik Nur Muftiyanto (Global Leadership Organizational Research in Management, 2024)
The development of entrepreneurs in Indonesia is increasingly making competition tight, therefore companies are required to implement a good strategy system for the products they sell. This study was conducted to determine the effect of service quality factors, product completeness, and price on consumer buying interest in retail-based companies. This research was conducted using quantitative methods and as many as 104 respondents. Data collection using a questionnaire and tested using the SPSS 25 application. The technique used Purposive sampling is one part of Non-probability sampling.